2011
DOI: 10.1130/b30410.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the history of sediment deposition in caves: A case study from Wonderwerk Cave, South Africa

Abstract: Reconstructing the history of sediment deposition in caves: A case study from Email alerting services articles cite this article to receive free e-mail alerts when new www.gsapubs.org/cgi/alerts click Subscribe America Bulletin to subscribe to Geological Society of www.gsapubs.org/subscriptions/ click Permission request to contact GSA http://www.geosociety.org/pubs/copyrt.htm#gsa click official positions of the Society. citizenship, gender, religion, or political viewpoint. Opinions presented in this publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 52 publications
2
39
0
4
Order By: Relevance
“…S4 and Table S1) (25). The Normal event can therefore be assigned to the Jaramillo subchron (1.07-0.99 Ma), a time range that fits with current understanding of the chronological position of the early Acheulean within the ESA in Southern Africa (28).…”
Section: Wonderwerk Cavesupporting
confidence: 66%
See 1 more Smart Citation
“…S4 and Table S1) (25). The Normal event can therefore be assigned to the Jaramillo subchron (1.07-0.99 Ma), a time range that fits with current understanding of the chronological position of the early Acheulean within the ESA in Southern Africa (28).…”
Section: Wonderwerk Cavesupporting
confidence: 66%
“…and reanalyzed the archaeological record of the site (24,25). Details on the archaeological, lithological, and chronological stratigraphy of excavation 1 are given in SI Text and illustrated in Figs.…”
Section: Wonderwerk Cavementioning
confidence: 99%
“…The dating is perhaps the least secure part of the evidence, since a possible reversed interval in the upper sequence (Chazan et al 2008) has not been confirmed (Matmon et al 2012), placing the main emphasis on cosmogenic nuclide dates. Although these support the early age, they are each presented with very large statistical errors, being of the order 1.09 0.2 Ma (Matmon et al 2012) allowing the outside possibility of a later date. Together, however, Swartkrans and Wonderwerk present a very similar picture, attested by different lines of evidence and analyses.…”
Section: Evidence Of Early Fire the Archaeological Recordmentioning
confidence: 99%
“…Além da obtenção de idades mínimas para alguns estágios de evolução de sistemas de condutos (Häuselmann e Granger, 2005), estes estudos veem permitindo a quantificação de taxas de incisão fluvial (Granger et al, 1997;Stock et al, 2004, Liu et al, 2013 e ainda um balizamento geocronológico para a evolução do modelado a partir das formas de relevo regionais Antony & Granger, 2007;Refsnider, 2010;Wagner et al, 2011;Matmon et al, 2012;Tassy et al, 2013).…”
Section: Aplicações Em Geociênciasunclassified